Innovations research as benefits of global consumer system - Михайлишин, Лілія Іванівна (Technology audit and production reserves, 2016)
The priority of innovations as a factor of economic development of any modem country is not the only their correct characteristics. Innovations beyond its economic nature are beneﬁts, which determine the evolution of civilization, and their quality components have signiﬁcant impact on the dynamics of this evolution. The article presents complex study on the positioning of innovative science and technology in the global consumption system, as well as their establishment in this system and the inability to transformation. The author has proved the following: innovations as beneﬁts of the global economic system make adjustments to the structure of the Maslow pyramid of modern man and their further development will make their own corrections. In the global consumption system we should single out innovations as beneﬁts of ﬁnal consumption and innovation as good of industrial purpose. The work established that innovation consumption regardless of their nature is in accordance with consumer utility, cost and public perception. Providing directions and criteria of formation of innovative economic development of Ukraine in terms of European integration are deﬁned. Based on comparative and analytical methods individual approaches to understanding innovation in the system of global consumption are deﬁned. The assumption of certain factors (parity of public perception and value) in the sphere of formation of economic relations in the global consumption of innovative products is made. The article has proved, that in global system of consumption innovations are treated as beneﬁts, and their distribution is more dependent on the capabilities of their purchase rather than generated from social progress. When establishing parity in public perception and acquisition opportunities development of innovation undergoes synergistic effect and promotes the transformation of social needs. The results of the research can be used by state and regional power, scientiﬁc-research establishments, management of domestic companies as well as by specialized organizations which function for stimulation of the processes of innovation activity development in Ukraine, as describing the strategic goals of further development of the respective areas.